Contribution to the Understanding of the Colour Change in Bluish-Grey Limestones - Silva, Teresa (2022)
ABSTRACT: Bluish-grey limestones have been extensively used as ornamental stones for decoration purposes in buildings, as well as in works of art, and accordingly, have been the target of intense exploration. In Portugal, the Jurassic limestone massif known as the Macico Calcario Estremenho (MCE), has been the source of grey-coloured ornamental stones, namely the Azul Valverde (one of the most well-known bluish-grey limestones) and Atlantic Blue varieties, both of which may undergo colour changes in outdoor environments. In this sense, it is important to understand the sudden colour change from bluish-grey to yellow/beige in the same limestone block in a quarry, or even, what happens to the colour when polished limestone is placed outdoors. This study was undertaken using various techniques, namely XRF (X-ray fluorescence spectrometry), XRD (X-ray diffraction), SEM (scanning electron microscopy), DTA-TG (differential thermal analysis/thermogravimetry) and colourimetry. Synchrotron radiation was also used at the European Synchrotron Radiation Facility (ESRF, Grenoble, France) where XANES (X-ray Absorption Near Edge Structure) spectra at Fe K-edge were collected to ascertain the speciation state of Fe in different coloured zones of the limestone, previously checked by EDXRF (energy dispersive X-ray fluorescence). The presence of Fe2+ and Fe3+ are responsible for the greyish and yellow/brown colour, respectively. On the other hand, the UV radiation from the sun causes a quickened and severe bleaching/fading on the dark blue/grey polished limestone.